Method for preparing aluminum sulfate and magnesium sulfate from magnesium-aluminum spinel waste

CN123002882APending Publication Date: 2026-10-30ZHEJIANG MEICHEN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611410921.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明提供了一种镁铝尖晶石废料制备硫酸铝和硫酸镁的方法,解决现有镁铝尖晶石废料利用率低、污染环境的问题

Benefits of technology

(1)本发明通过预处理有效去除了废料中的铁、硅等主要杂质,增大废料比表面积,配合水热酸解反应,进一步促进镁铝尖晶石溶解,为后续除杂和产品纯度提供了保障。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to waste resource utilization and inorganic chemical product preparation field, especially to a kind of method for preparing aluminium sulfate and magnesium sulfate from magnesium-aluminum spinel waste.The method comprises: pretreating magnesium-aluminum spinel waste to obtain pretreated magnesium-aluminum spinel waste;mixing pretreated magnesium-aluminum spinel waste and sulfuric acid solution to carry out hydrothermal acidolysis reaction under sulfuric acid condition to obtain hydrothermal reaction liquid and filter residue;removing impurities from hydrothermal reaction liquid to obtain mixed solution containing magnesium sulfate and aluminium sulfate;adding fluoride to the mixed solution to carry out first reaction to obtain magnesium fluoride precipitate and aluminium sulfate solution;mixing the magnesium fluoride precipitate and sulfuric acid solution to carry out second reaction to obtain magnesium sulfate;crystallizing and purifying aluminium sulfate solution to obtain aluminium sulfate.The present application solves the problems of low utilization rate and environmental pollution of magnesium-aluminum spinel waste and realizes the double resource utilization of magnesium and aluminum in magnesium-aluminum spinel waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waste resource utilization and inorganic chemical product preparation, and particularly to a method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste. Background Technology

[0002] Magnesium aluminum spinel (MgAl2O4), as a high-performance novel inorganic non-metallic material, possesses high melting point, high hardness, and good chemical and thermodynamic stability, making it widely used in refractory materials, ceramics, metallurgy, electronic packaging, aerospace, and other fields. However, the production and processing of MgAl2O4 products, as well as its disposal after service, generate a large amount of waste. This waste typically contains over 70% MgAl2O4, along with oxide impurities such as Fe2O3, SiO2, CaO, MgO, and MnO, as well as trace amounts of heavy metals such as Zn, Cu, Cr, and Ni. Currently, this waste is mostly disposed of through stockpiling or landfilling, which not only occupies significant land resources but also causes soil and water pollution due to the infiltration of soluble impurities, while simultaneously wasting the aluminum and magnesium resources contained within.

[0003] In recent years, magnesium-aluminum spinel waste has attracted attention due to its high aluminum content. However, existing methods mostly employ traditional ambient temperature and pressure acid leaching processes, which have significant technical bottlenecks: on the one hand, the dense crystal structure of magnesium-aluminum spinel results in slow and incomplete acid leaching reactions at ambient temperature and pressure, with raw material conversion rates typically below 30%, making effective acid hydrolysis of aluminum and magnesium impossible; on the other hand, the presence of a large amount of MgO in the waste means that the post-acid hydrolysis solution also contains large amounts of magnesium sulfate and aluminum sulfate, both of which are soluble components, making efficient separation difficult and severely restricting the separate recovery and purification of aluminum and magnesium. Furthermore, there is a lack of effective means for the simultaneous removal of impurities such as Fe2O3, SiO2, CaO, and heavy metal ions.

[0004] Therefore, developing a process route that is simple, thoroughly removes impurities (especially heavy metals), and enables the resource utilization of magnesium aluminum spinel waste has significant economic, social, and environmental benefits. Summary of the Invention

[0005] This invention provides a method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste, solving the problems of low utilization rate and environmental pollution of existing magnesium aluminum spinel waste.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention provides a method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste, comprising the following steps: S1. Pre-treat the magnesium aluminum spinel waste to obtain pre-treated magnesium aluminum spinel waste; S2. The pretreated magnesium aluminum spinel waste is mixed with sulfuric acid solution and subjected to hydrothermal acid hydrolysis reaction to obtain hydrothermal reaction liquid and filter residue. S3. Remove impurities from the hydrothermal reaction solution to obtain a mixed solution containing magnesium sulfate and aluminum sulfate; S4. Add fluoride to the mixed solution to carry out the first reaction, and obtain magnesium fluoride precipitate and aluminum sulfate solution; mix the magnesium fluoride precipitate and sulfuric acid solution to carry out the second reaction, and obtain magnesium sulfate. S5. The aluminum sulfate solution is purified by crystallization to obtain aluminum sulfate.

[0007] In some specific embodiments, in S1, the preprocessing includes: The magnesium aluminum spinel waste is crushed to a particle size ≤20mm, and then successively ground, magnetically separated to remove iron, and alkaline washed to remove silicon to obtain a reaction solution. The reaction solution is then subjected to solid-liquid separation to obtain a solid product, which is then washed and dried.

[0008] In some specific embodiments, the grinding method is ball milling, and the ball milling conditions are: time of 2-4 hours, ball-to-material ratio of 8:1-10:1, and rotation speed of 300-500 r / min. The conditions for magnetic separation to remove iron are: magnetic separation intensity of 0.2~0.4T, temperature of 10~30℃, number of magnetic separations of 2~3, and single magnetic separation time of 10~20min; The alkaline washing process for removing silicon includes: mixing the waste material after magnetic separation for iron removal with an alkaline solution and then performing alkaline washing; The alkaline solution is a sodium hydroxide solution with a concentration of 0.3~0.8 mol / L. The liquid-to-solid ratio of the alkaline solution to the waste material after magnetic separation is (8-12):1 mL / g. The alkaline washing conditions are: temperature 50~70℃ and time 1~2 h.

[0009] In some specific embodiments, in S2, the liquid-to-solid ratio of the pretreated magnesium aluminum spinel waste to the sulfuric acid solution is (5~15):1mL / g, and the concentration of the sulfuric acid solution is 1.5~3mol / L; the conditions for the hydrothermal acidolysis reaction are: temperature 120~200℃, time 2~8h, and pressure 0.2~1MPa.

[0010] In some specific embodiments, in S3, the impurity removal includes: iron removal by oxidation, silicon removal by flocculation, heavy metal removal, and impurity removal by ion exchange.

[0011] In some specific embodiments, the oxidation and iron removal process includes: An oxidant is added to the hydrothermal reaction solution to adjust the pH to acidic, and an oxidation reaction is carried out to obtain a solution after iron removal. The amount of oxidant added is 0.3% to 0.8% of the mass of the hydrothermal reaction solution; the oxidant includes at least one of hydrogen peroxide, sodium hypochlorite, and potassium permanganate; the conditions for the oxidation reaction are: temperature 40 to 60°C, time 30 to 60 min; The flocculation and desiliconization process includes: A flocculant is added to the iron-removed solution to carry out a flocculation reaction, and then the solution is allowed to settle to obtain a silicon-removed solution. The amount of flocculant added is 0.1% to 0.3% of the mass of the solution after iron removal; the flocculant includes at least one of polyaluminum chloride, polyacrylamide, and ferrous sulfate; the conditions for the flocculation reaction are: temperature of 30 to 50°C and time of 20 to 40 minutes; the settling time is 30 to 60 minutes.

[0012] In some specific embodiments, the heavy metal removal process includes: A heavy metal chelating agent is added to the desiliconized solution obtained after flocculation and desiliconization to carry out a chelation reaction, thereby obtaining a heavy metal-free solution. The amount of the heavy metal chelating agent added is 0.2% to 0.5% of the mass of the solution after silicon removal; the heavy metal chelating agent includes at least one of dithiocarbamate, chelating resin and sodium sulfide; the chelation reaction conditions are: temperature 40 to 60°C, time 30 to 45 min. The ion exchange purification process includes: The solution after heavy metal removal is passed through a cation exchange resin column to obtain a mixed solution of magnesium sulfate and aluminum sulfate. The cation exchange resin includes a strong acid styrene-based cation exchange resin; the diameter-to-height ratio of the cation exchange resin column is 1:5 to 1:10; and the flow rate of the solution after heavy metal removal is 1 to 3 BV / h.

[0013] In some specific embodiments, in S4, the amount of fluoride added is equal to the amount of Mg in the mixed solution. 2+ The amount is 1.0 to 1.2 times the theoretical stoichiometric amount; the fluoride includes at least one of sodium fluoride, potassium fluoride, and hydrofluoric acid; the conditions for the first reaction are: temperature of 50 to 70°C and time of 60 to 90 min; the mass ratio of the magnesium fluoride precipitate to the sulfuric acid solution is 1:1.2 to 1:1.5, and the concentration of the sulfuric acid solution is 92 wt% to 98 wt%; the time for the second reaction is 1 to 2 h.

[0014] In some specific embodiments, in S5, the crystallization and purification process includes: The aluminum sulfate solution was successively evaporated, concentrated, and cooled to crystallize, resulting in a crystallization system. The crystallization system was then subjected to solid-liquid separation to obtain aluminum sulfate crystals, which were subsequently washed and dried.

[0015] In some specific embodiments, the evaporation and concentration conditions are as follows: concentration at a temperature of 80~100℃ and a vacuum degree of 0.05~0.08MPa until the aluminum sulfate solution concentration is 35wt%~45wt%. The cooling crystallization method is gradient cooling crystallization; the conditions for gradient cooling crystallization are: first, cooling to 40-50℃ at a rate of 5-10℃ / h, holding at a constant temperature for 1-2h, and then cooling to 20-30℃ at a rate of 2-5℃ / h, holding at a constant temperature for 4-8h.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention effectively removes the main impurities such as iron and silicon in the waste through pretreatment, increases the specific surface area of ​​the waste, and further promotes the dissolution of magnesium aluminum spinel in conjunction with hydrothermal acid hydrolysis reaction, thus providing a guarantee for subsequent impurity removal and product purity.

[0017] (2) This invention promotes the dissolution of magnesium aluminum spinel through hydrothermal acid hydrolysis reaction, transforming the waste that was originally piled up and polluted the environment into high-value-added aluminum sulfate and magnesium sulfate products, fully recovering both magnesium and aluminum resources, realizing the dual resource utilization of magnesium aluminum spinel waste, reducing land occupation and environmental pollution, and having both environmental and economic benefits.

[0018] (3) The impurity removal process of this invention is highly targeted and has a good impurity removal effect. It can not only completely remove conventional impurities, but also effectively remove heavy metals such as Zn, Cu, Cr, and Ni, ensuring product purity ≥99.5% and guaranteeing product safety.

[0019] (4) This invention achieves magnesium removal by introducing fluoride to generate magnesium fluoride precipitate, which can ensure the purity of the final aluminum sulfate product. At the same time, the process of generating magnesium fluoride precipitate and regenerating magnesium sulfate with sulfuric acid improves the utilization rate of magnesium resources.

[0020] (5) The present invention is simple to operate and easy to industrialize and produce on a large scale; at the same time, the product has high purity, aluminum sulfate meets the requirements of high-end industrial applications, and magnesium sulfate can be used in agriculture, chemical industry and other fields. It has broad market prospects and can be widely used in water treatment, papermaking, printing and dyeing, agriculture and other industries. Detailed Implementation

[0021] The present invention will be described below through specific embodiments. Those skilled in the art will understand that the specific embodiments described below are for illustrative purposes only and do not limit the scope of the invention in any way. Furthermore, in the following embodiments, unless otherwise specified, the reagents and equipment used are commercially available. If specific processing conditions and methods are not explicitly described in the following embodiments, conditions and methods known in the art can be used for processing.

[0022] This invention provides a method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste, comprising the following steps: S1. Pre-treat the magnesium aluminum spinel waste to obtain pre-treated magnesium aluminum spinel waste; S2. The pretreated magnesium aluminum spinel waste is mixed with sulfuric acid solution and subjected to hydrothermal acid hydrolysis reaction to obtain hydrothermal reaction liquid and filter residue. S3. Remove impurities from the hydrothermal reaction solution to obtain a mixed solution containing magnesium sulfate and aluminum sulfate; S4. Add fluoride to the mixed solution to carry out the first reaction, and obtain magnesium fluoride precipitate and aluminum sulfate solution; mix the magnesium fluoride precipitate and sulfuric acid solution to carry out the second reaction, and obtain magnesium sulfate. S5. The aluminum sulfate solution is purified by crystallization to obtain aluminum sulfate.

[0023] This invention discloses a method for preparing aluminum sulfate and magnesium sulfate from magnesium-aluminum spinel waste. By optimizing the pretreatment process, hydrothermal reaction, and impurity removal processes of the magnesium-aluminum spinel waste, and utilizing a high-temperature, high-pressure hydrothermal environment to promote the dissolution of magnesium-aluminum spinel, the method achieves dual resource utilization of magnesium and aluminum in the waste (converting them into aluminum sulfate and magnesium sulfate). Simultaneously, it recovers and utilizes magnesium fluoride precipitate to prepare high-purity aluminum sulfate products, reducing production costs, minimizing environmental pollution, removing heavy metal impurities, and ensuring product safety. In detail: Pretreatment of magnesium-aluminum spinel waste removes some impurities (such as iron and silicon), increases the specific surface area of ​​the waste, and ensures the subsequent dissolution and hydrothermal acidification reaction of magnesium-aluminum spinel under high temperature and high pressure, thereby improving the reaction conversion rate and reaction rate. Then, hydrothermal acidification is used to promote the dissolution of magnesium-aluminum spinel, ensuring that MgAl2O4 in the pretreated waste reacts completely with sulfuric acid to generate soluble aluminum sulfate and magnesium sulfate, achieving efficient leaching and preliminary resource utilization of aluminum and magnesium. The resulting hydrothermal solution is then purified to remove all impurities (Fe2O4, Fe2O4, and Fe3O4) from the hydrothermal reaction solution. 3+ Fe 2+ Ca 2+ Mg 2+ SiO3 2- Mn2+ The process involves removing impurities such as heavy metals (Zn, Cu, Cr, Ni, etc.) to obtain a mixed solution of aluminum sulfate and magnesium sulfate, ensuring the purity and safety of subsequent products. The magnesium sulfate and aluminum sulfate solution is then subjected to magnesium precipitation separation, and magnesium fluoride precipitate is recycled to prepare magnesium sulfate, further realizing magnesium resource recovery. The aluminum sulfate solution is then converted into high-purity aluminum sulfate crystals, and water and residual trace soluble impurities are removed from the solution to obtain aluminum sulfate products that meet the requirements of high-end industrial applications.

[0024] In some embodiments, in S1, the mass content of MgAl2O4 in the magnesium aluminum spinel waste is ≥70%, and the impurities in the magnesium aluminum spinel waste include Fe2O3, SiO2, CaO, MgO, MnO, Zn, Cu, Cr and Ni.

[0025] In some embodiments, in S1, the preprocessing includes: The magnesium aluminum spinel waste is crushed to a particle size ≤20mm, and then successively ground, magnetically separated to remove iron, and alkaline washed to remove silicon to obtain a reaction solution. The reaction solution is then subjected to solid-liquid separation to obtain a solid product, which is then washed and dried.

[0026] In this invention, magnesium aluminum spinel waste is sequentially crushed, ground, magnetically separated to remove iron, and alkali washed to remove silicon. Crushing and grinding increase the specific surface area of ​​the magnesium aluminum spinel waste, improving its contact area with sulfuric acid solution. Combined with the hydrothermal acidolysis reaction, this further accelerates the dissolution rate of the magnesium aluminum spinel and the hydrothermal acidolysis reaction. Magnetic separation removes iron by utilizing the magnetic properties of Fe2O3, using a high-intensity magnetic separator to separate and remove iron impurities from the waste, preventing them from entering the subsequent reaction system and affecting product purity. Alkali washing removes silicon by reacting SiO2 with a strong alkali (NaOH) to generate soluble sodium silicate (Na2SiO3), which is then separated and removed by filtration. The reaction equation is as follows: SiO2 + 2NaOH → Na2SiO3 + H2O.

[0027] In some embodiments, the crushing to a particle size ≤20mm is performed. The crushing method is not specifically limited and can be carried out in a jaw crusher. In this invention, crushing the magnesium aluminum spinel waste to a particle size ≤20mm removes large impurities (such as soil and stones) from the waste, facilitating subsequent grinding.

[0028] In some embodiments, the grinding is performed to a particle size ≤100μm. In this invention, the grinding method is not specifically limited; any conventional method in the art can be used to grind to a particle size ≤100μm. In some embodiments, the grinding method includes: mixing crushed magnesium aluminum spinel waste with water, ball milling, separating the slurry by vacuum filtration after ball milling, and drying the resulting solid product; the ball milling conditions are: time 2~4h, ball-to-material ratio 8:1~10:1, and rotation speed 300-500r / min. In this invention, the surface area of ​​the waste powder after grinding is increased, allowing it to fully contact the sulfuric acid solution. Combined with the subsequent high-temperature and high-pressure hydrothermal environment, this can significantly promote the dissolution of magnesium aluminum spinel.

[0029] In some embodiments, the iron impurity content in the magnesium-aluminum spinel waste after magnetic separation is ≤0.5wt%. In this invention, the conditions for magnetic separation are not specifically limited; conventional magnetic separation conditions in the art can be used to ensure that the iron impurity content in the magnesium-aluminum spinel waste is ≤0.5wt%. In some embodiments, the conditions for magnetic separation are: magnetic separation intensity of 0.2~0.4T, temperature of 10~30℃, single magnetic separation time of 10~20min, and 2~3 magnetic separation cycles.

[0030] In some embodiments, the alkaline washing process for removing silicon includes: mixing the waste material after magnetic separation for iron removal with an alkaline solution and performing alkaline washing.

[0031] In some embodiments, the alkaline solution is a sodium hydroxide solution with a concentration of 0.3~0.8 mol / L, the liquid-to-solid ratio of the alkaline solution to the waste material after magnetic separation is (8-12) mL:1 g, and the alkaline washing conditions are: temperature of 50~70℃ and time of 1~2 h.

[0032] In this invention, if the concentration of sodium hydroxide solution in the alkaline washing for silicon removal is too high, it will cause Al2O3 in the waste to react and be lost prematurely; if the concentration is too low, the silicon removal will be incomplete.

[0033] In some embodiments, the pretreatment process includes solid-liquid separation: cooling the reaction solution to 10~30°C and performing vacuum filtration to obtain a filter cake.

[0034] In some embodiments, the pretreatment process includes washing the filter cake with water until the pH of the filtrate reaches 7.0 ± 0.2, repeating the washing 2-3 times. The amount of water used in each wash is 2-3 times the mass of the filter cake, to remove residual NaOH and sodium silicate from the filter cake surface. After washing, the filter cake is dried for later use. The SiO2 content in the pretreated waste is ≤0.3%. The improved purity of the pretreated waste further promotes subsequent dissolution and acidolysis reactions under high temperature and high pressure hydrothermal conditions.

[0035] In some embodiments, in S2, the mixing conditions are: a stirring speed of 10~30 r / min and a stirring time of 30~60 min.

[0036] In this invention, by uniformly mixing the pretreated magnesium aluminum spinel waste with sulfuric acid solution, incomplete local reactions are avoided, laying the foundation for the full dissolution of magnesium aluminum spinel under high temperature and high pressure hydrothermal environment.

[0037] In some embodiments, in S2, the liquid-to-solid ratio of the pretreated magnesium aluminum spinel waste to the sulfuric acid solution is (5~15):1mL / g.

[0038] In some embodiments, in S2, the concentration of the sulfuric acid solution is 1.5~3 mol / L. In this invention, by controlling the concentration of the sulfuric acid solution within the above range, combined with high-temperature and high-pressure hydrothermal conditions, the conversion rate can reach over 90%, and the reaction is mild. If the concentration of the sulfuric acid solution is too high, the reaction will be too violent, generating a large amount of heat, damaging the equipment, and increasing the difficulty of subsequent impurity removal; if the concentration is too low, the reaction rate will be slow, and even under high-temperature and high-pressure hydrothermal conditions, it will be difficult to promote the full dissolution of magnesium aluminum spinel, resulting in a low magnesium aluminum spinel conversion rate.

[0039] In some embodiments, the conditions for the hydrothermal acidolysis reaction in S2 are: temperature of 120~200℃, time of 2~8h, and pressure of 0.2~1MPa.

[0040] In this invention, magnesium aluminum spinel (MgAl2O4) has a dense crystal structure, making it difficult to dissolve in acid at room temperature and pressure. However, high-temperature and high-pressure hydrothermal conditions can significantly reduce the activation energy of the reaction, effectively promoting the dissolution of magnesium aluminum spinel, destroying its dense crystal structure, and causing MgAl2O4 to undergo a metathesis reaction with sulfuric acid. 3+ and Mg 2+ The magnesium and aluminum are dissociated and combine with sulfate ions to form soluble aluminum sulfate (Al2(SO4)3) and magnesium sulfate (MgSO4), thus achieving the initial resource utilization of magnesium and aluminum. The reaction equation is as follows: MgAl2O4+4H2SO4→Al2(SO4)3+MgSO4+4H2O.

[0041] It is evident that the high-temperature, high-pressure hydrothermal environment is crucial for promoting the dissolution of magnesium aluminum spinel. By controlling the hydrothermal acidolysis reaction conditions within the aforementioned range, not only can the dissolution of magnesium aluminum spinel be promoted, the reaction rate accelerated, and the reaction made more thorough, thus improving the conversion rate of magnesium aluminum spinel waste, but the hydrothermal environment can also reduce sulfuric acid volatilization, thereby reducing acid consumption and environmental pollution. If the reaction temperature is too low (<120℃), the crystal structure of magnesium aluminum spinel is difficult to destroy, resulting in insufficient dissolution and a low conversion rate; if the temperature is too high (>200℃), energy consumption increases, and sulfuric acid volatilization is aggravated. The reaction pressure should be matched with the temperature; excessive pressure will increase equipment costs and safety risks. If the reaction time is too short (<2h), the reaction will be incomplete; if the time is too long (>8h), energy consumption will increase, resulting in poor economic benefits. As a preferred method, the hydrothermal acidolysis reaction conditions are: temperature 150~180℃, time 4~6h, and pressure 0.5~0.8MPa. Under these preferred conditions, the dissolution of magnesium aluminum spinel can be promoted to the greatest extent, allowing MgAl2O4 to fully dissociate and generate aluminum sulfate and magnesium sulfate.

[0042] In some embodiments, during S2, the hydrothermal acidolysis reaction is continuously stirred at a speed of 10-30 r / min.

[0043] In this invention, after the hydrothermal acid hydrolysis reaction in step S2, a post-treatment is also included. The post-treatment includes: after the hydrothermal acid hydrolysis reaction, the obtained product is naturally cooled to 10~30℃ and vacuum filtered to obtain a hydrothermal reaction solution and filter residue. The hydrothermal reaction solution contains aluminum sulfate, magnesium sulfate and a small amount of impurities. The filter residue is unreacted magnesium aluminum spinel and insoluble impurities (such as MnO). The filter residue is washed with deionized water 2~3 times, and the washing liquid is added to the hydrothermal reaction solution. The filter residue is returned to S2 to undergo a new hydrothermal acid hydrolysis reaction to improve the raw material utilization rate. The final raw material conversion rate is ≥92%, achieving efficient leaching of magnesium and aluminum elements.

[0044] In some embodiments, S3 includes: iron removal by oxidation, silicon removal by flocculation, heavy metal removal, and impurity removal by ion exchange.

[0045] In some embodiments, the process of oxidative iron removal includes: adding an oxidant to the hydrothermal reaction solution, adjusting the pH to acidic, carrying out an oxidation reaction, and obtaining an iron-removed solution.

[0046] In some embodiments, the amount of oxidant added is 0.3% to 0.8% of the mass of the hydrothermal reaction solution.

[0047] In some embodiments, the oxidant includes at least one of hydrogen peroxide, sodium hypochlorite, and potassium permanganate, preferably hydrogen peroxide, which does not cause secondary pollution.

[0048] In some embodiments, the target pH value is 2.0 to 3.5, and sulfuric acid solution can be used to adjust the pH.

[0049] In some embodiments, the oxidation reaction is carried out under the following conditions: temperature of 40-60°C and time of 30-60 min.

[0050] In some embodiments, the oxidation reaction is continuously stirred at a speed of 10-30 r / min.

[0051] In this invention, the principle of the oxidation reaction is that the oxidant oxidizes Fe in the solution. 2+ Oxidized to Fe 3+ Fe 3+ Hydrolysis within a pH range of 2.0-3.5 produces a sparingly soluble Fe(OH)3 precipitate, which is removed by filtration. The reaction equation is as follows (using hydrogen peroxide as an example): 2Fe 2+ +H₂O₂ + 2H₂ + →2Fe 3+ +2H2O; Fe 3+ +3H₂O→Fe(OH)₃↓+3H + .

[0052] In some embodiments, after the oxidation reaction is completed, the method further includes: vacuum filtering the obtained product to remove the Fe(OH)3 precipitate, obtaining a solution after iron removal, wherein the Fe in the solution is... 3+ Content ≤0.01%.

[0053] In some embodiments, the flocculation and desiliconization process includes: A flocculant is added to the iron-removed solution to induce a flocculation reaction, and then the solution is allowed to settle to obtain a silicon-removed solution.

[0054] In some embodiments, the amount of flocculant added is 0.1% to 0.3% of the mass of the solution after iron removal.

[0055] In some embodiments, the flocculant includes at least one of polyaluminum chloride (PAC), polyacrylamide (PAM), and ferrous sulfate; preferably polyaluminum chloride and polyacrylamide, the combination of polyaluminum chloride and polyacrylamide has excellent flocculation effect.

[0056] In some embodiments, the conditions for the flocculation reaction are: temperature of 30~50℃ and time of 20~40min.

[0057] In some embodiments, the flocculation reaction is continuously stirred at a speed of 10-30 r / min.

[0058] In some embodiments, the settling time is 30-60 minutes.

[0059] In this invention, the principle of the flocculation reaction is that the flocculant forms a colloid in the solution, adsorbing trace amounts of residual SiO3 in the solution. 2- This causes it to polymerize and form silica colloids, which then coagulate and settle, and silicon impurities are removed by filtration.

[0060] In some embodiments, after the flocculation reaction is completed, the method further includes: vacuum filtering the obtained reaction product to remove the silica precipitate and obtain a desiliconized solution with a SiO2 content ≤0.005%.

[0061] In some embodiments, the heavy metal removal process includes: A heavy metal chelating agent is added to the desiliconized solution obtained after flocculation and desiliconization to carry out a chelation reaction, thereby obtaining a heavy metal-free solution.

[0062] In some embodiments, the amount of the heavy metal catching agent added is 0.2% to 0.5% of the mass of the solution after silicon removal.

[0063] In some embodiments, the heavy metal trapping agent includes at least one of dithiocarbamate, chelating resin, and sodium sulfide.

[0064] In some embodiments, the chelation reaction is performed under the following conditions: temperature of 40-60°C and time of 30-45 min.

[0065] In some embodiments, the chelation reaction is continuously stirred at a speed of 10-30 r / min.

[0066] In this invention, the principle of chelation reaction is that the heavy metal scavenger molecule contains functional groups that can bind with heavy metal ions (Zn, Cu, Cr, Ni), which can chelate with trace amounts of heavy metal ions in the solution to generate stable, water-insoluble chelate precipitates, which are then removed by filtration to avoid heavy metal impurities affecting product quality and environmental safety.

[0067] In some implementations, after the chelation reaction is completed, the following steps are also taken: the obtained product is vacuum filtered to remove the heavy metal chelate precipitate, and a solution after heavy metal removal is obtained. The contents of Zn, Cu, Cr and Ni in the solution are all ≤0.0005%, ensuring the quality of subsequent products and environmental safety.

[0068] In some embodiments, the ion exchange purification process includes: The solution after heavy metal removal is passed through a cation exchange resin column to obtain a mixed solution of magnesium sulfate and aluminum sulfate.

[0069] In some embodiments, the cation exchange resin includes a strongly acidic styrene-based cation exchange resin, preferably of type 001×7.

[0070] In some embodiments, the diameter-to-height ratio of the cation exchange resin column is 1:5 to 1:10; the flow rate of the solution after heavy metal removal is 1 to 3 BV / h, where BV is the volume of the cation exchange resin column.

[0071] In this invention, the principle of ion exchange for impurity removal is based on the presence of H+ in the strongly acidic cation exchange resin. + With trace amounts of Fe remaining in the solution 3+ Ca 2+ Mg 2+ Mn 2+ When metal ions undergo an exchange reaction, they are adsorbed onto the resin. + When it enters the solution, it does not affect the purity of aluminum sulfate, thus ensuring the preparation of high-purity aluminum sulfate products.

[0072] In some embodiments, the content of each metal ion in the magnesium sulfate and aluminum sulfate mixed solution is ≤0.003%.

[0073] In some embodiments, when the adsorption capacity of the cation exchange resin column reaches saturation, it is regenerated using a 5wt%~8wt% sulfuric acid solution at a regeneration temperature of 40-60℃ and a regeneration flow rate of 1-2 BV / h. The regenerated solution is returned to S2 as a replenishment solution for the sulfuric acid solution, thereby achieving resource recycling and reducing acid consumption.

[0074] In some embodiments, in S4, the amount of fluoride added is equal to the amount of Mg in the mixed solution. 2+ 1.0 to 1.2 times the theoretical measurement.

[0075] In some embodiments, S4, the fluoride includes at least one of sodium fluoride, potassium fluoride, and hydrofluoric acid.

[0076] In some embodiments, in S4, the conditions for the first reaction are: a temperature of 50~70°C and a time of 60~90 min.

[0077] In some embodiments, during S4, stirring is continuously performed during the first reaction process, and the stirring speed is 10~30 r / min.

[0078] In this invention, in S4, the principle of the first reaction is Mg 2+ With F - Combined to form MgF2 precipitate (Ksp=7.4×10). -11 This precipitate is poorly soluble in water and can be completely removed by filtration.

[0079] In some embodiments, S4, after the first reaction is completed, further includes: filtering the obtained product to obtain precipitated magnesium fluoride and aluminum sulfate solution.

[0080] In some embodiments, in S4, the mass ratio of the magnesium fluoride precipitate to the sulfuric acid solution is 1:1.2 to 1:1.5, and the concentration of the sulfuric acid solution is 92wt% to 98wt%.

[0081] In some embodiments, in S4, the sulfuric acid solution may be selected from industrial-grade concentrated sulfuric acid solution or industrial waste concentrated sulfuric acid solution after impurity removal and concentration.

[0082] In some embodiments, in S4, the second reaction takes 1 to 2 hours.

[0083] In some embodiments, in S4, after the second reaction is completed, HF gas is also generated. The HF can be further utilized after being condensed and recovered. That is, magnesium fluoride precipitate and sulfuric acid solution generate magnesium sulfate and HF gas through the second reaction.

[0084] In some embodiments, S4, after the second reaction is completed, further includes: filtering the product obtained after the second reaction to obtain a magnesium sulfate solution, and then subjecting the magnesium sulfate solution to evaporation concentration, cooling crystallization, and drying to obtain a magnesium sulfate product with a purity ≥98.5%, thereby achieving further recovery of magnesium resources; wherein, the evaporation concentration conditions are: concentrating to a concentration of 40wt%~50wt% at a temperature of 85~95℃ and a vacuum of 0.05~0.08MPa; the cooling crystallization conditions are: cooling to 25~35℃ for crystallization for 3~5h; and the drying conditions are: a temperature of 100~110℃ for 1~3h.

[0085] In some embodiments, S5, the crystallization and purification process includes: The aluminum sulfate solution was successively evaporated, concentrated, and cooled to crystallize, resulting in a crystallization system. The crystallization system was then subjected to solid-liquid separation to obtain aluminum sulfate crystals, which were subsequently washed and dried.

[0086] In this invention, a pure aluminum sulfate solution is evaporated and concentrated to increase the concentration of aluminum sulfate in the solution. Then, by cooling and crystallization, aluminum sulfate is precipitated in the form of Al2(SO4)3·18H2O crystals, while a small amount of residual soluble impurities remain in the solution. Through solid-liquid separation, washing, and drying, high-purity aluminum sulfate crystals are obtained.

[0087] In some embodiments, the evaporation and concentration conditions are as follows: concentration at a temperature of 80~100°C and a vacuum of 0.05~0.08 MPa until the aluminum sulfate solution concentration is 35wt%~45wt%.

[0088] In this invention, vacuum evaporation can lower the evaporation temperature, avoid the decomposition of aluminum sulfate, and accelerate the evaporation rate; concentration is stopped when the solution concentration is 35%-45% (mass fraction), at which point the solution is in a supersaturated state, which facilitates subsequent crystallization.

[0089] In some embodiments, the cooling crystallization method is gradient cooling crystallization; the conditions for gradient cooling crystallization are: first, cooling to 40-50°C at a rate of 5-10°C / h, holding at a constant temperature for 1-2 hours, and then cooling to 20-30°C at a rate of 2-5°C / h, holding at a constant temperature for 4-8 hours.

[0090] In this invention, gradient cooling can prevent crystallization from being too fast, which can lead to uneven crystal size and inclusion of impurities, thereby improving crystal purity and appearance quality. If the crystallization temperature is too low (<20℃), impurities such as magnesium sulfate will crystallize out along with the crystals, affecting product purity. If the temperature is too high (>30℃), the crystallization rate will be slow and the production efficiency will be low.

[0091] In some embodiments, in step S5, the crystals are washed 2-3 times with deionized water, with the amount of water used each time being 1-2 times the mass of the crystals, until no SO4 is present in the washing solution. 2- (Tested with barium chloride solution, no white precipitate was found), removing impurities and residual solution adsorbed on the crystal surface.

[0092] In some embodiments, in S5, the drying conditions are: temperature of 100~120°C, time of 2~4h, until the water content of the aluminum sulfate crystals is ≤0.5wt%.

[0093] In this invention, if the drying temperature is too high (>120℃), the aluminum sulfate crystals will lose their water of crystallization, affecting the product quality; if the temperature is too low (<100℃), the drying will be incomplete, and the crystals will easily absorb moisture and deteriorate; drying can be done by vacuum drying or hot air drying, with vacuum drying being preferred because it has a better drying effect and can avoid crystal oxidation.

[0094] In some embodiments, step S5 further includes: after drying, cooling to room temperature, collecting the crystals to obtain a high-purity aluminum sulfate product. The aluminum sulfate product is a white needle-like crystal with a purity ≥99.5%, wherein Fe... 3+ Content ≤0.005%, Ca 2 + Content ≤0.003%, Mg 2+ The content is ≤0.003%, SiO2 content is ≤0.002%, and Zn, Cu, Cr and Ni content are all ≤0.0005%, which meets the first-grade standard of GB / T3151-2016 "Industrial Aluminum Sulfate".

[0095] This invention achieves dual resource utilization of magnesium-aluminum spinel waste. A combined pretreatment process involving crushing, grinding, magnetic separation for iron removal, and alkaline washing for silicon removal effectively removes major impurities such as iron and silicon and increases the specific surface area. Then, a high-temperature, high-pressure hydrothermal environment is used to disrupt the dense crystal structure of the magnesium-aluminum spinel, enabling efficient dissolution with a fast reaction rate and an aluminum-magnesium raw material conversion rate exceeding 95%. This process is energy-efficient and reduces sulfuric acid volatilization. Subsequently, a multi-stage impurity removal process involving oxidation for iron removal, flocculation for silicon removal, heavy metal removal, and ion exchange for deep impurity removal thoroughly removes conventional impurities and heavy metals such as Zn, Cu, Cr, and Ni. Magnesium is removed by introducing fluorides to generate magnesium fluoride precipitate, ensuring aluminum sulfate purity ≥99.5% while recovering magnesium resources. The resulting magnesium fluoride precipitate reacts with industrial-grade concentrated sulfuric acid or industrial waste sulfuric acid to prepare magnesium sulfate, releasing HF, which is then volatilized, condensed, and reused in the magnesium precipitation step, achieving internal fluorine circulation and effectively reducing operating costs. The filter residue is returned to the hydrothermal reaction step for reuse, and the ion exchange resin regeneration liquid is used as a sulfuric acid solution replenishment liquid, further reducing raw material consumption and production costs. The entire process has clear parameters, mild reaction conditions, and moderate equipment requirements, which facilitates large-scale industrial production. The resulting high-purity aluminum sulfate and magnesium sulfate products can be widely used in water treatment, papermaking, printing and dyeing, agriculture and other fields, with broad market prospects and significant environmental and economic benefits.

[0096] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments. The embodiments of this application are only examples, and all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0097] Example 1 The specific steps for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste are as follows: S1. Select magnesium aluminum spinel waste (MgAl2O4 content 75%, Fe2O3 content 2.3%, SiO2 content 3.1%, CaO content 1.2%, MgO content 4.5%, MnO content 0.8%, Zn content 0.002%, Cu content 0.0015%, Cr content 0.001%, Ni content 0.0008%), and crush it to a particle size ≤20mm in a jaw crusher; transfer it to a ball mill, add deionized water, and grind it for 3 hours at a ball-to-material ratio of 9:1 and a speed of 400r / min until the particle size ≤100μm. Vacuum filter and dry to obtain waste powder; send the waste powder to a high-intensity magnetic separator, with a magnetic separation temperature of 25℃, a magnetic separation intensity of 0.3T, and two magnetic separations for 15 minutes each to remove iron impurities; mix the magnetically separated waste powder with 0.5mol / L... NaOH solution was mixed at a liquid-to-solid ratio of 10:1 mL / g and transferred to a reaction vessel. The mixture was stirred at 60℃ and 25 r / min for 1.5 h, then vacuum filtered. The filter cake was washed with deionized water, using twice the mass of the filter cake for each wash. The mixture was washed three times until the pH of the washing solution reached 7.0. The product was then dried to obtain the pretreated waste material (SiO2 content 0.25%, Fe2O3 content 0.4%).

[0098] S2. The pretreated waste material was mixed with 2.2 mol / L sulfuric acid solution at a liquid-to-solid ratio of 10:1 mL / g and stirred at 15 r / min for 45 min. The mixture was then transferred to a hydrothermal reactor, sealed, and heated to 160℃. The pressure was controlled at 0.6 MPa, the stirring speed at 20 r / min, and the reaction was carried out for 5 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and then vacuum filtered to obtain the hydrothermal reaction solution and filter residue. The filter residue was washed twice with deionized water, and the washing liquid was added to the hydrothermal reaction solution. The filter residue was returned to S2 for re-reaction. The raw material conversion rate was 93.2%.

[0099] S3. Add hydrogen peroxide (0.5% of the mass of the hydrothermal reaction solution) to the hydrothermal reaction solution, stir well, adjust the pH to 3.0 with dilute sulfuric acid, stir at 50℃ and 25r / min for 45min, vacuum filter, discard the Fe(OH)3 precipitate, and obtain the iron-removed solution (Fe 3+The content is 0.008%; PAC (0.2% of the mass of the iron-removed solution) is added to the iron-removed solution, stirred evenly, stirred at 40℃ and 15r / min for 30min, allowed to stand and settle for 45min, vacuum filtered, and the precipitate is discarded to obtain the silicon-removed solution (SiO2 content 0.004%); dithiocarbamate (0.3% of the mass of the silicon-removed solution) is added to the silicon-removed solution, stirred evenly, stirred at 50℃ and 25r / min for 40min, vacuum filtered, and the heavy metal chelate precipitate is discarded to obtain the heavy metal-removed solution (Zn content 0.0003%, Cu content 0.0002%, Cr content 0.0001%, Ni content 0.0001%); the heavy metal-removed solution is passed through a 001×7 type strong acid cation exchange resin column (diameter-to-height ratio 1:8) at a controlled flow rate of 2BV / h to obtain a pure aluminum sulfate and magnesium sulfate mixed solution (Fe 3+ Ca 2+ Mg 2+ Mn 2+ The content of all components is ≤0.002%); the strongly acidic cation exchange resin column is regenerated using a 6wt% sulfuric acid solution at a regeneration temperature of 40℃ and a regeneration flow rate of 1.8 BV / h, and the regenerated solution is returned to S2. S4. Add NaF (MgO) to the purified solution. 2+ The mixture was stirred thoroughly at 1.1 times the theoretical molar ratio, and then stirred at 60℃ and 25 r / min for 75 min. Vacuum filtration was performed to obtain magnesium fluoride precipitate (MgF2 precipitate) and aluminum sulfate solution. The MgF2 precipitate was washed twice with deionized water, and the washings were added to the aluminum sulfate solution. The washed MgF2 precipitate was transferred to an acid-resistant reactor, and 98 wt% industrial-grade concentrated sulfuric acid solution was added. The MgF2 and concentrated sulfuric acid solution were mixed at a mass ratio of 1:1.3, and the mixture was stirred at room temperature and pressure for 1.5 h to generate magnesium sulfate solution and HF gas (HF was recovered by condensation). The magnesium sulfate solution was then filtered for later use. S5. Transfer the pure crude aluminum sulfate solution to a vacuum evaporation and concentration device, concentrate it to a concentration of 40 wt% at 90℃ and a vacuum degree of 0.06 MPa; transfer it to a crystallization kettle, cool it to 45℃ at a rate of 8℃ / h, hold it at this temperature for 1.5h, then cool it to 25℃ at a rate of 3℃ / h, and hold it at this temperature for 6h; vacuum filter to obtain aluminum sulfate crystals; wash the crystals twice with deionized water, each time using 1.5 times the mass of the crystals, until the washing liquid is free of SO4. 2- The crystals were placed in a vacuum drying oven and dried at 110°C for 3 hours. After cooling to room temperature, the aluminum sulfate product was collected. Meanwhile, the magnesium sulfate solution obtained in S4 was concentrated to 45 wt% at 90°C and 0.06 MPa, cooled to 30°C for 4 hours to crystallize, filtered, washed, and dried at 105°C for 2 hours to obtain the magnesium sulfate product.

[0100] Testing revealed that the aluminum sulfate product is a white needle-like crystal with a purity of 99.7%, containing Fe. 3+ Content 0.003%, Ca 2+ Content 0.002%, Mg 2+ The content is 0.002%, SiO2 content is 0.001%, Zn content is 0.0003%, Cu content is 0.0002%, Cr content is 0.0001%, and Ni content is 0.0001%, which meets the first-grade standard of GB / T3151-2016 "Industrial Aluminum Sulfate"; the magnesium sulfate product has a purity of 98.8%, which meets the industrial magnesium sulfate standard, realizing the dual resource utilization of magnesium and aluminum.

[0101] Example 2 The specific steps for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste are as follows: S1. Select magnesium aluminum spinel waste (MgAl2O4 content 72%, Fe2O3 content 2.8%, SiO2 content 3.5%, CaO content 1.5%, MgO content 5.1%, MnO content 1.0%, Zn content 0.0025%, Cu content 0.0018%, Cr content 0.0012%, Ni content 0.0009%), and crush it in a jaw crusher to a particle size ≤20mm; transfer it to a ball mill, add deionized water, and grind it for 2.5h at a ball-to-material ratio of 8:1 and a speed of 350r / min until the particle size ≤100μm. Vacuum filter and dry to obtain waste powder; send the waste powder to a high-intensity magnetic separator, with a magnetic separation temperature of 25℃, a magnetic separation intensity of 0.25T, and magnetic separation 3 times, 12min each time, to remove iron impurities; mix the magnetically separated waste powder with 0.6mol / L NaOH solution was mixed at a liquid-to-solid ratio of 11:1 mL / g and transferred to a reaction vessel. The mixture was stirred at 65℃ and 28 r / min for 1.2 h, then vacuum filtered. The filter cake was washed with deionized water, using twice the mass of the filter cake for each wash. The washing was repeated three times until the pH of the washing solution reached 7.1. The mixture was then dried to obtain the pretreated waste material (Fe2O3 content 0.45%, SiO2 content 0.28%).

[0102] S2. The pretreated waste material was mixed with 2.5 mol / L sulfuric acid solution at a liquid-to-solid ratio of 12:1 mL / g and stirred at 20 r / min for 40 min. The mixture was then transferred to a hydrothermal reactor, sealed, and heated to 170℃. The pressure was controlled at 0.7 MPa, the stirring speed at 25 r / min, and the reaction was carried out for 4.5 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and then vacuum filtered to obtain the hydrothermal reaction solution and filter residue. The filter residue was washed twice with deionized water, and the washing liquid was added to the hydrothermal reaction solution. The filter residue was returned to S2 for re-reaction, and the raw material conversion rate was 92.8%.

[0103] S3. Add sodium hypochlorite (0.6% of the mass of the hydrothermal reaction solution) to the hydrothermal reaction solution, stir well, adjust the pH to 2.8 with dilute sulfuric acid, stir at 55℃ and 28 r / min for 40 min, vacuum filter, discard the Fe(OH)3 precipitate, and obtain the iron-removed solution (Fe 3+ The content is 0.009%; PAM (0.25% of the mass of the iron-removed solution) is added to the iron-removed solution, stirred evenly, stirred at 45℃ and 18r / min for 35min, allowed to stand and settle for 50min, vacuum filtered, and the precipitate is discarded to obtain the silicon-removed solution (SiO2 content 0.0035%); chelating resin (0.4% of the mass of the silicon-removed solution, chelating resin is iminodiacetic acid chelating resin) is added to the silicon-removed solution, stirred at 55℃ and 28r / min for 42min, vacuum filtered, and the heavy metal chelate precipitate is discarded to obtain the heavy metal-removed solution (Zn content 0.00025%, Cu content 0.00018%, Cr content 0.00012%, Ni content 0.00009%); the heavy metal-removed solution is passed through a 001×7 type strong acid cation exchange resin column (diameter-to-height ratio 1:9) at a controlled flow rate of 2.2 BV / h to obtain a pure aluminum sulfate and magnesium sulfate crude solution (Fe 3+ Ca 2+ Mg 2+ Mn 2+ The content of all components is ≤0.0025%); the strong acid cation exchange resin column is regenerated with 7wt% sulfuric acid solution at a regeneration temperature of 45℃ and a regeneration flow rate of 1.5 BV / h, and the regenerated solution is returned to S2.

[0104] S4. Add KF (MgO) to the purified solution. 2+ The mixture was stirred thoroughly at 65℃ and 28 rpm for 80 min, then vacuum filtered to obtain magnesium fluoride precipitate (MgF2 precipitate) and aluminum sulfate solution. The MgF2 precipitate was washed twice with deionized water, and the washings were added to the aluminum sulfate solution. The washed MgF2 precipitate was transferred to an acid-resistant reactor, and a concentrated industrial waste sulfuric acid solution with a concentration of 95.4 wt% was added. The MgF2 and waste sulfuric acid solution were mixed at a mass ratio of 1:1.4 and stirred at room temperature and pressure for 1.6 h to generate magnesium sulfate solution and HF gas (HF was recovered by condensation). The magnesium sulfate solution was filtered for later use. The precipitate was washed twice with deionized water, and the washings were added to the solution to obtain a pure crude aluminum sulfate solution (MgF2 precipitate). 2+ Content 0.009%) S5. Transfer the pure crude aluminum sulfate solution to a vacuum evaporation and concentration apparatus, concentrate it to a concentration of 42 wt% at 95℃ and a vacuum degree of 0.07 MPa; transfer it to a crystallization kettle, cool it to 48℃ at a rate of 9℃ / h, hold it at that temperature for 1.2h, then cool it to 28℃ at a rate of 4℃ / h, and hold it at that temperature for 5h; vacuum filter to obtain aluminum sulfate crystals; wash the crystals three times with deionized water, each time using 1.2 times the mass of the crystals, until the washing liquid is free of SO4. 2- The crystals were placed in a hot air drying oven and dried at 115°C for 2.5 hours. After cooling to room temperature, the aluminum sulfate product was collected. Meanwhile, the magnesium sulfate solution obtained in S4 was concentrated to 48 wt% at 92°C and 0.07 MPa, cooled to 32°C for 3.5 hours to crystallize, filtered, washed, and dried at 108°C for 2 hours to obtain the magnesium sulfate product.

[0105] Testing revealed that the aluminum sulfate product is a white needle-like crystal with a purity of 99.6%, containing Fe. 3+ Content 0.004%, Ca 2+ Content 0.0025%, Mg 2+ The product contains 0.0028% aluminum sulfate, 0.0015% SiO2, 0.00025% Zn, 0.00018% Cu, 0.00012% Cr, and 0.00009% Ni, meeting the first-grade standard of GB / T3151-2016 "Industrial Aluminum Sulfate"; the magnesium sulfate product has a purity of 98.7%, meeting the industrial magnesium sulfate standard, thus realizing the dual resource utilization of magnesium and aluminum.

[0106] Example 3 The specific steps for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste are as follows: S1. Select magnesium aluminum spinel waste (MgAl2O4 content 78%, Fe2O3 content 1.9%, SiO2 content 2.7%, CaO content 0.9%, MgO content 3.8%, MnO content 0.6%, Zn content 0.0018%, Cu content 0.0012%, Cr content 0.0009%, Ni content 0.0007%), and crush it in a jaw crusher to a particle size ≤20mm; transfer it to a ball mill, add deionized water, and grind it for 3.5h at a ball-to-material ratio of 10:1 and a rotation speed of 450r / min until the particle size ≤100μm. Vacuum filter and dry to obtain waste powder; send the waste powder to a high-intensity magnetic separator, with a magnetic separation temperature of 25℃, a magnetic separation intensity of 0.35T, and two magnetic separations, each lasting 18min, to remove iron impurities; mix the magnetically separated waste powder with 0.4mol / L... NaOH solution was mixed at a liquid-to-solid ratio of 9:1 mL / g and transferred to a reaction vessel. The mixture was stirred at 55℃ and 22 r / min for 1.8 h, then vacuum filtered. The filter cake was washed with deionized water, using twice the mass of the filter cake for each wash. The washing was repeated three times until the pH of the washing solution reached 6.9. The mixture was then dried to obtain the pretreated waste material (Fe2O3 content 0.35%, SiO2 content 0.22%).

[0107] S2. The pretreated waste material was mixed with 2.0 mol / L sulfuric acid solution at a liquid-to-solid ratio of 8:1 mL / g and stirred at 20 r / min for 50 min. The mixture was then transferred to a hydrothermal reactor, sealed, and heated to 150℃. The pressure was controlled at 0.5 MPa, and the stirring speed was 20 r / min. The mixture was reacted for 6 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and then vacuum filtered to obtain the hydrothermal reaction solution and filter residue. The filter residue was washed twice with deionized water, and the washing liquid was added to the hydrothermal reaction solution. The filter residue was returned to S2 for re-reaction. The raw material conversion rate was 93.5%.

[0108] S3. Add potassium permanganate (0.4% of the mass of the hydrothermal reaction solution) to the hydrothermal reaction solution, stir well, adjust the pH to 3.2 with dilute sulfuric acid, stir at 45℃ and 22r / min for 50min, vacuum filter, discard the Fe(OH)3 precipitate, and obtain the iron-removed solution (Fe 3+The content is 0.007%); add PAC and PAM compound flocculant (mass ratio 1:1, total addition amount is 0.15% of the mass of the iron-removed solution) to the iron-removed solution, stir at 35℃ and 12r / min for 25min, let stand and settle for 40min, vacuum filter, discard the precipitate, and obtain the silicon-removed solution (SiO2 content 0.003%); add sodium sulfide (addition amount is 0.3% of the mass of the silicon-removed solution) to the silicon-removed solution, stir evenly, and at 45℃... The mixture was stirred at 22 rpm for 35 min at ℃, then vacuum filtered to remove the heavy metal chelate precipitate, yielding a solution with removed heavy metals (Zn content 0.0002%, Cu content 0.00015%, Cr content 0.00008%, Ni content 0.00008%). This solution was then passed through a 001×7 type strong acid cation exchange resin column (diameter-to-height ratio 1:7) at a controlled flow rate of 1.8 BV / h to obtain a crude solution of pure aluminum sulfate and magnesium sulfate (Fe). 3+ Ca 2+ Mg 2+ Mn 2+ The content of all components is ≤0.0018%); the strongly acidic cation exchange resin column is regenerated with 5.5wt% sulfuric acid solution at a regeneration temperature of 50℃ and a regeneration flow rate of 1.6 BV / h, and the regenerated solution is returned to S2.

[0109] S4. Add NaF (MgO) to the purified solution. 2+ (1.15 times the theoretical molar ratio), stirred evenly, stirred at 55℃ and 22r / min for 70min, vacuum filtered to obtain magnesium fluoride precipitate (MgF2 precipitate) and aluminum sulfate solution; the MgF2 precipitate was washed twice with deionized water, and the washing liquid was added to the aluminum sulfate solution. The washed MgF2 precipitate was transferred to an acid-resistant reactor, and 98wt% industrial grade concentrated sulfuric acid solution was added. MgF2 and concentrated sulfuric acid solution were mixed at a mass ratio of 1:1.2, and stirred at room temperature and pressure for 1.2h to generate magnesium sulfate solution and HF gas (HF was recovered by condensation). The magnesium sulfate solution was filtered for later use; the precipitate was washed twice with deionized water, and the washing liquid was added to the solution to obtain a pure crude aluminum sulfate solution (MgF2 precipitate). 2+ Content 0.007%) S5. Transfer the pure crude aluminum sulfate solution to a vacuum evaporation and concentration device, concentrate it to a concentration of 38 wt% at 85℃ and a vacuum degree of 0.05 MPa; transfer it to a crystallization kettle, cool it to 42℃ at a rate of 7℃ / h, hold it at this temperature for 1.8h, then cool it to 22℃ at a rate of 2.5℃ / h, and hold it at this temperature for 7h; vacuum filter to obtain aluminum sulfate crystals; wash the crystals twice with deionized water, each time using 1.8 times the mass of the crystals, until the washing liquid is free of SO4. 2-The crystals were placed in a vacuum drying oven and dried at 105°C for 3.5 hours. After cooling to room temperature, the aluminum sulfate product was collected. Meanwhile, the magnesium sulfate solution obtained in S4 was concentrated to 42 wt% at 88°C and 0.05 MPa, cooled to 28°C and crystallized for 4.5 hours. After filtration, washing, and drying at 102°C for 2.5 hours, the magnesium sulfate product was obtained.

[0110] Testing revealed that the aluminum sulfate product is a white needle-like crystal with a purity of 99.8%, containing Fe. 3+ Content 0.0025%, Ca 2+ Content 0.0018%, Mg 2+ The product contains 0.0015% aluminum sulfate, 0.001% SiO2, 0.0002% Zn, 0.00015% Cu, 0.00008% Cr, and 0.00008% Ni, meeting the first-grade standard of GB / T3151-2016 "Industrial Aluminum Sulfate"; the magnesium sulfate product has a purity of 99.0%, meeting the industrial magnesium sulfate standard, thus realizing the dual resource utilization of magnesium and aluminum.

[0111] Example 4 The specific steps for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste are as follows: S1. Select magnesium aluminum spinel waste (MgAl2O4 content 70%, Fe2O3 content 3.2%, SiO2 content 3.8%, CaO content 1.8%, MgO content 5.5%, MnO content 1.2%, Zn content 0.003%, Cu content 0.002%, Cr content 0.0015%, Ni content 0.001%), and crush it in a jaw crusher to a particle size ≤20mm; transfer it to a ball mill, add deionized water, and grind it for 2.8h at a ball-to-material ratio of 8.5:1 and a rotation speed of 380r / min until the particle size ≤100μm. Vacuum filter and dry to obtain waste powder; send the waste powder to a high-intensity magnetic separator, with a magnetic separation temperature of 25℃, a magnetic separation intensity of 0.32T, and magnetic separation 3 times, 14min each time, to remove iron impurities; mix the magnetically separated waste powder with 0.7mol / L NaOH solution was mixed at a liquid-to-solid ratio of 11.5:1 mL / g and transferred to a reaction vessel. The mixture was stirred at 68℃ and 26 r / min for 1.4 h, then vacuum filtered. The filter cake was washed with deionized water, using twice the mass of the filter cake for each wash. The washing was repeated three times until the pH of the washing solution reached 7.2. The mixture was then dried to obtain the pretreated waste material (Fe2O3 content 0.48%, SiO2 content 0.30%).

[0112] S2. The pretreated waste material was mixed with 2.8 mol / L sulfuric acid solution at a liquid-to-solid ratio of 14:1 mL / g and stirred at 20 r / min for 35 min. The mixture was then transferred to a hydrothermal reactor, sealed, and heated to 180℃. The pressure was controlled at 0.8 MPa, the stirring speed at 25 r / min, and the reaction was carried out for 4 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and then vacuum filtered to obtain the hydrothermal reaction solution and filter residue. The filter residue was washed twice with deionized water, and the washing liquid was added to the hydrothermal reaction solution. The filter residue was returned to S2 for re-reaction. The raw material conversion rate was 92.5%.

[0113] S3. Add a mixed oxidant of hydrogen peroxide and sodium hypochlorite (mass ratio 2:1, total addition amount is 0.7% of the mass of the hydrothermal reaction solution), adjust the pH to 2.5 with dilute sulfuric acid, stir at 58℃ and 26 r / min for 35 min, vacuum filter, discard the Fe(OH)3 precipitate, and obtain the iron-removed solution (Fe 3+ The content is 0.010%); ferrous sulfate (0.28% of the mass of the iron-removed solution) is added to the iron-removed solution, stirred evenly at 48℃ and 16r / min for 38min, allowed to settle for 55min, vacuum filtered, and the precipitate is discarded to obtain the silicon-removed solution (SiO2 content 0.0045%); a mixed chelating agent of dithiocarbamate and chelating resin (mass ratio 3:1, total addition amount is 0.45% of the solution mass) is added, stirred at 58℃ and 26r / min for 43min, vacuum filtered, and the heavy metal chelate precipitate is discarded to obtain the heavy metal-removed solution (Zn content 0.0003%, Cu content 0.0002%, Cr content 0.00015%, Ni content 0.0001%); the heavy metal-removed solution is passed through a 001×7 type strong acid cation exchange resin column (diameter-to-height ratio 1:10) at a controlled flow rate of 2.5 BV / h to obtain a pure aluminum sulfate and magnesium sulfate crude solution (Fe 3+ Ca 2+ Mg 2+ Mn 2+ The content of all components is ≤0.003%); the strongly acidic cation exchange resin column is regenerated with 7.5wt% sulfuric acid solution at a regeneration temperature of 50℃ and a regeneration flow rate of 1.8 BV / h, and the regenerated solution is returned to S2.

[0114] S4. Add KF (MgO) to the purified solution. 2+The mixture was stirred thoroughly at 68℃ and 26 r / min for 85 min, then vacuum filtered to obtain magnesium fluoride precipitate (MgF2 precipitate) and aluminum sulfate solution. The MgF2 precipitate was washed twice with deionized water, and the washing liquid was added to the aluminum sulfate solution. The washed MgF2 precipitate was transferred to an acid-resistant reactor, and concentrated industrial waste sulfuric acid solution (concentration 92.3 wt%) was added. MgF2 and waste sulfuric acid solution were mixed at a mass ratio of 1:1.5, and the mixture was stirred at room temperature and pressure for 1.8 h to generate magnesium sulfate solution and HF gas (HF was recovered by condensation). The magnesium sulfate solution was filtered for later use. The precipitate was washed three times with deionized water, and the washing liquid was added to the solution to obtain a pure crude aluminum sulfate solution (MgF2 precipitate). 2+ Content 0.010%) S5. Transfer the pure crude aluminum sulfate solution to a vacuum evaporation and concentration apparatus, concentrate it to a concentration of 44 wt% at 98℃ and a vacuum degree of 0.075 MPa; transfer it to a crystallization kettle, cool it to 49℃ at a rate of 10℃ / h, hold it at that temperature for 1.1h, then cool it to 29℃ at a rate of 4.5℃ / h, and hold it at that temperature for 4.5h; vacuum filter to obtain aluminum sulfate crystals; wash the crystals three times with deionized water, each time using 1.1 times the mass of the crystals, until the washing liquid is free of SO4. 2- The crystals were placed in a hot air drying oven and dried at 118°C for 2.2 hours. After cooling to room temperature, the aluminum sulfate product was collected. At the same time, the magnesium sulfate solution obtained from S4 was concentrated to 49% at 94°C and 0.075 MPa, cooled to 34°C and crystallized for 3.2 hours. After filtration, washing, and drying at 110°C for 1.8 hours, the magnesium sulfate product was obtained.

[0115] Testing revealed that the aluminum sulfate product is a white needle-like crystal with a purity of 99.5%, containing Fe. 3+ Content 0.005%, Ca 2+ Content 0.003%, Mg 2+ The product contains 0.003% aluminum sulfate, 0.002% SiO2, 0.0003% Zn, 0.0002% Cu, 0.00015% Cr, and 0.0001% Ni, meeting the first-grade standard of GB / T3151-2016 "Industrial Aluminum Sulfate"; the magnesium sulfate product has a purity of 98.6%, meeting the standard of industrial magnesium sulfate, thus realizing the dual resource utilization of magnesium and aluminum.

[0116] Comparative Example 1 (no high-temperature and high-pressure hydrothermal reaction, acid leaching at room temperature and pressure) A method for preparing aluminum sulfate from magnesium aluminum spinel waste differs from that in Example 1 in the following steps: S2, the pretreated waste is mixed with 2.2 mol / L sulfuric acid solution at a liquid-to-solid ratio of 10:1 mL / g, stirred at 25 r / min for 45 min until homogeneous; the mixture is then transferred to a conventional reactor and stirred for 12 h at ambient temperature and pressure (25℃, 0.1 MPa) (extending the reaction time to compensate for the lack of high temperature and pressure); after the reaction, the mixture is vacuum filtered to obtain an acid leaching reaction solution and filter residue; the filter residue is washed twice with deionized water, and the washing liquid is added to the acid leaching reaction solution, while the filter residue is returned to this step for re-reaction; at this point, the raw material conversion rate is only 35.1% (far lower than 93.2% in Example 1). Due to the lack of a high temperature and pressure hydrothermal environment, the crystal structure of magnesium aluminum spinel is not effectively destroyed, dissolution is insufficient, and the leaching rate of magnesium and aluminum elements is extremely low. The rest is consistent with that in Example 1, yielding aluminum sulfate and magnesium sulfate products.

[0117] Testing revealed that the acid hydrolysis conversion rate of magnesium-aluminum spinel waste was only 35.1%. A large amount of magnesium-aluminum spinel failed to effectively dissolve and release magnesium and aluminum under normal temperature and pressure acid leaching conditions, resulting in a large amount of residue containing magnesium-aluminum spinel. Furthermore, the purity of the obtained aluminum sulfate product was only 94.7%, and the purity of the magnesium sulfate product was 92.1%, with both yields less than 35% of that in Example 1, indicating insufficient recovery of magnesium and aluminum resources.

[0118] It is evident that a high-temperature, high-pressure hydrothermal environment is crucial for promoting the dissolution of magnesium aluminum spinel, improving raw material conversion rate, and increasing product purity. Without a high-temperature, high-pressure hydrothermal reaction, the feasibility of the process decreases significantly, and both product quality and yield cannot meet the standards.

[0119] Comparative Example 2 (Precipitation-free magnesium and fluorine removal and recycling steps) The method for preparing aluminum sulfate from magnesium aluminum spinel waste includes the following steps: S1, raw material pretreatment, is exactly the same as S1 in Example 1.

[0120] S2, hydrothermal acid hydrolysis reaction, is exactly the same as S2 in Example 1, with a raw material conversion rate of 93.2%.

[0121] S3, multi-stage impurity removal using hydrothermal solution, is exactly the same as S3 in Example 1.

[0122] S4. Without the steps of precipitation to remove magnesium and recycling fluorine, magnesium remains in the aluminum sulfate solution.

[0123] S5. Aluminum sulfate crystallization and purification, which is exactly the same as step 5 in Example 1 (preparation of magnesium sulfate-free product).

[0124] Testing revealed that the aluminum sulfate product had a purity of only 57.2%. Because magnesium was not recovered through precipitation separation, a large amount of magnesium sulfate was present in the aluminum sulfate product. Furthermore, no magnesium sulfate was produced, resulting in a significant decrease in economic benefits.

[0125] It is evident that the high-temperature, high-pressure hydrothermal process is crucial for ensuring the complete acid hydrolysis of highly stable magnesium aluminum spinel to produce a mixed solution of aluminum sulfate and magnesium sulfate. Furthermore, by adding fluoride for magnesium precipitation, the purity of the final aluminum sulfate product can be ensured, while also enabling magnesium recovery. Simultaneously, the HF released during the precipitation of magnesium fluoride to form magnesium sulfate can be recovered through condensation and recycled for further magnesium removal, resulting in significant economic and environmental benefits.

[0126] Besides the magnesium fluoride precipitate used in this patent, magnesium can also be separated by filtration through the formation of magnesium carbonate precipitate, magnesium phosphate precipitate, and magnesium hydroxide precipitate. However, magnesium carbonate precipitation requires large amounts of sodium carbonate or sodium bicarbonate, and generates significant carbon dioxide emissions during the re-acidification process to generate magnesium sulfate, resulting in poor economic and environmental benefits. Magnesium phosphate precipitation requires large amounts of phosphoric acid, and the phosphate ions generated during the re-acidification process cannot be separated and removed, becoming impurities and affecting product purity. The magnesium hydroxide precipitation process requires large amounts of strong alkalis such as sodium hydroxide, and inevitably produces aluminum hydroxide precipitate during the formation of magnesium hydroxide precipitate, leading to inefficient and incomplete separation of magnesium and aluminum, affecting product purity, and the use of large amounts of strong alkalis results in high costs. The magnesium fluoride precipitate used in this patent removes magnesium. During the re-acidification process to generate magnesium sulfate, the HF generated can be recovered through condensation and reused to generate magnesium fluoride precipitate, allowing fluorine to be recycled within the system, resulting in better economic and environmental benefits.

[0127] Although preferred embodiments of the invention have been shown and described, it is conceivable that those skilled in the art can devise various modifications to the invention within the spirit and scope of the appended claims.

Claims

1. A method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste, characterized in that, Includes the following steps: S1. Pre-treat the magnesium aluminum spinel waste to obtain pre-treated magnesium aluminum spinel waste. S2. The pretreated magnesium aluminum spinel waste is mixed with sulfuric acid solution and subjected to hydrothermal acid hydrolysis reaction to obtain hydrothermal reaction liquid and filter residue. S3. Remove impurities from the hydrothermal reaction solution to obtain a mixed solution containing magnesium sulfate and aluminum sulfate; S4. Add fluoride to the mixed solution to carry out the first reaction, and obtain magnesium fluoride precipitate and aluminum sulfate solution; The magnesium fluoride precipitate and sulfuric acid solution are mixed to carry out a second reaction, yielding magnesium sulfate; S5. The aluminum sulfate solution is purified by crystallization to obtain aluminum sulfate.

2. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 1, characterized in that, In S1, the preprocessing includes: The magnesium aluminum spinel waste is crushed to a particle size ≤20mm, and then successively ground, magnetically separated to remove iron, and alkaline washed to remove silicon to obtain a reaction solution. The reaction solution is then subjected to solid-liquid separation to obtain a solid product, which is then washed and dried.

3. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 2, characterized in that, The grinding method is ball milling, and the ball milling conditions are: time of 2-4 hours, ball-to-material ratio of 8:1-10:1, and rotation speed of 300-500 r / min. The conditions for magnetic separation to remove iron are: magnetic separation intensity of 0.2~0.4T, temperature of 10~30℃, number of magnetic separations of 2~3, and single magnetic separation time of 10~20min; The alkaline washing process for removing silicon includes: mixing the waste material after magnetic separation for iron removal with an alkaline solution and then performing alkaline washing; The alkaline solution is a sodium hydroxide solution with a concentration of 0.3~0.8 mol / L. The liquid-to-solid ratio of the alkaline solution to the waste material after magnetic separation is (8-12):1 mL / g. The alkaline washing conditions are: temperature 50~70℃ and time 1~2 h.

4. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 1, characterized in that, In S2, the liquid-to-solid ratio of the pretreated magnesium aluminum spinel waste to the sulfuric acid solution is (5~15):1mL / g, and the concentration of the sulfuric acid solution is 1.5~3mol / L; the conditions for the hydrothermal acidolysis reaction are: temperature 120~200℃, time 2~8h, and pressure 0.2~1MPa.

5. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 1, characterized in that, In S3, the impurity removal includes: iron removal by oxidation, silicon removal by flocculation, heavy metal removal, and impurity removal by ion exchange.

6. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 5, characterized in that, The oxidation process for removing iron includes: An oxidant is added to the hydrothermal reaction solution to adjust the pH to acidic, and an oxidation reaction is carried out to obtain a solution after iron removal. The amount of oxidant added is 0.3% to 0.8% of the mass of the hydrothermal reaction solution; the oxidant includes at least one of hydrogen peroxide, sodium hypochlorite, and potassium permanganate; the conditions for the oxidation reaction are: temperature 40 to 60°C, time 30 to 60 min; The flocculation and desiliconization process includes: A flocculant is added to the iron-removed solution to carry out a flocculation reaction, and then the solution is allowed to settle to obtain a silicon-removed solution. The amount of flocculant added is 0.1% to 0.3% of the mass of the solution after iron removal; the flocculant includes at least one of polyaluminum chloride, polyacrylamide, and ferrous sulfate; the conditions for the flocculation reaction are: temperature of 30 to 50°C and time of 20 to 40 minutes; the settling time is 30 to 60 minutes.

7. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 5, characterized in that, The heavy metal removal process includes: A heavy metal chelating agent is added to the desiliconized solution obtained after flocculation and desiliconization to carry out a chelation reaction, thereby obtaining a heavy metal-free solution. The amount of the heavy metal chelating agent added is 0.2% to 0.5% of the mass of the solution after silicon removal; the heavy metal chelating agent includes at least one of dithiocarbamate, chelating resin and sodium sulfide; the chelation reaction conditions are: temperature 40 to 60°C, time 30 to 45 min. The ion exchange purification process includes: The solution after heavy metal removal is passed through a cation exchange resin column to obtain a mixed solution of magnesium sulfate and aluminum sulfate. The cation exchange resin includes a strong acid styrene-based cation exchange resin; the diameter-to-height ratio of the cation exchange resin column is 1:5 to 1:10; and the flow rate of the solution after heavy metal removal is 1 to 3 BV / h.

8. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 1, characterized in that, In S4, the amount of fluoride added is equal to the amount of Mg in the mixed solution. 2+ The amount of fluoride is 1.0 to 1.2 times the theoretical molar stoichiometry; the fluoride includes at least one of sodium fluoride, potassium fluoride, and hydrofluoric acid; the conditions for the first reaction are: temperature of 50 to 70°C and time of 60 to 90 min; the mass ratio of the magnesium fluoride precipitate to the sulfuric acid solution is 1:1.2 to 1:1.5, and the concentration of the sulfuric acid solution is 92 wt% to 98 wt%; the time for the second reaction is 1 to 2 h.

9. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 1, characterized in that, In S5, the crystallization and purification process includes: The aluminum sulfate solution was successively evaporated, concentrated, and cooled to crystallize, resulting in a crystallization system. The crystallization system was then subjected to solid-liquid separation to obtain aluminum sulfate crystals, which were subsequently washed and dried.

10. The method for preparing aluminum sulfate and magnesium sulfate from magnesium aluminum spinel waste according to claim 9, characterized in that, The evaporation and concentration conditions are as follows: concentration at a temperature of 80~100℃ and a vacuum degree of 0.05~0.08MPa until the aluminum sulfate solution concentration is 35wt%~45wt%. The cooling crystallization method is gradient cooling crystallization; the conditions for gradient cooling crystallization are: first, cooling to 40-50℃ at a rate of 5-10℃ / h, holding at a constant temperature for 1-2h, and then cooling to 20-30℃ at a rate of 2-5℃ / h, holding at a constant temperature for 4-8h.